Multiple primary malignant neoplasm: Case report and comprehensive literature review - Ma, Xue-Yan; Tian, Kun; Sun, Peng-Fei (Frontiers in Oncology, 2023)
Multiple primary tumors, especially quadruple primary tumors, are extremely rare clinically, and there is no standard protocol for clinical management. We described a case in which a bone tumor, a malignant bladder tumor, a malignant melanoma, and an intrahepatic cholangiocarcinoma were all original malignancies. The patient is a 79-year-old woman who underwent surgery for a left middle finger bone tumor 45 years ago, as well as surgery for bladder malignancy and postoperative adjuvant chemotherapy 15 years ago, and the precise pathological results and treatment are unclear. One year ago, she underwent amputation of the toe due to a black mass of the right toe and was diagnosed pathologically as a freckled malignant melanoma of the extremity. Prior to postoperative adjuvant systemic medication, PET/CT revealed malignancy in the lateral segment of the left lobe of the liver, and multiple lymphadenopathies in the left parotid gland, hilar hepatic, and retroperitoneal region. Intrahepatic cholangiocarcinoma was found in the liver puncture biopsy’s pathology report. The serum sample’s next-generation sequencing (NGS) revealed a missense mutation, designated P.G12V, in exon 2 of the KRAS gene. Based on patients with malignant melanoma and intrahepatic cholangiocarcinoma, she received 6 cycles of GP (gemcitabine/cisplatin) combined with Camrelizumab systemic therapy, and followed by 3 cycles of Camrelizumab maintenance therapy, the efficacy was evaluated as stable disease (SD) during treatment. When the 4th cycle of Camrelizumab was suggested for maintenance therapy, the efficacy evaluation revealed that the tumor had greatly advanced. The patient refused to continue anti-tumor therapy and passed away from septic shock and multiple organ failure 3 months later. The patient had satisfactory efficacy and lived for a year after being diagnosed with two primary cancers. Despite the rarity of quadruple primary tumors and the lack of a conventional clinical management strategy, we postulate that germline mutations in the KRAS gene may be closely associated with the formation and development of multiple primary tumors. NGS testing is necessary for clinical management, and systemic treatment based on concurrent multiple main tumors is the key to improving prognosis.